Enhancing mechanical properties and corrosion resistance of nickel-aluminum bronze via hot rolling process. (20th January 2021) - Zeng, Yanhua; Yang, Fenfen; Chen, Zongning; Guo, Enyu; Gao, Minqiang; Wang, Xuejian; Kang, Huijun; Wang, Tongmin
Abstract: The mechanical properties and corrosion behavior of as-cast, as-annealed and hot-rolled nickel-aluminum bronze (NAB) alloy (Cu-9Al-10Ni-4Fe-1.2 Mn, all in wt.%) in 3.5 wt.% NaCl solution were investigated. The results show that annealing introduces a large number of κ phases to precipitate in the α phase. However, after further hot rolling, the original continuous κ phases are spheroidized and dispersed, increasing the strength, hardness, and elongation of the alloy. In addition to the enhanced mechanical properties, the corrosion resistance of the NAB samples is also improved significantly by hot rolling, as revealed by the mass loss measurements, electrochemical impedance spectroscopy (EIS), and cross-sectional corrosion morphology. Selective phase corrosion occurs by the preferential corrosion of the α phase, which acts as an anode to the κ phases, and the uncorroded κ phases are retained in the corrosion product film. The interfaces between the κ phases and the surrounding corrosion products become discontinuous caused by the spheroidization of κ phases, reducing the corrosion of the substrate by the corrosive medium via the channels. As a result, the corrosion rate and the maximum local corrosion depth of the hot-rolled NAB sample are greatly reduced.